Genetic divergence for infestation of chrysomelid beetle (Nisotra orbiculata) in kenaf (Hibiscus cannabinus) - PANDIT, N C; GOSWAMI, K K; KUMAR, D (The Indian Journal of Agricultural Sciences, 2013)
Forty-two gelmplasms of kenaf (Hibiscus cannabinus L.) collected earlier from different Parts of India and abroadwere evaluated to study the genetic divergence for infestation of chrysomelid beetle [Nisotra arbiculata (Mots.)]. Data onaverage infestation at 3 different seedling stages were scored and were analysed following D2 analysis. The strains weregrouped into 9 different clusters, of which cluster IV accommodated a large number of &trains (15 strains) having different geographical origin. The clustering pattern of the varieties did not follow the geographical origin. Genetic drift and selection in different environments seems to cause greater diversity. Hybridization among the strains from diverse clusters may help in producing resistance to the chrysomelid beetle. The strains with low average infestationmay beused as parents for backcross breeding.